Analisis Framing Berita Pemberhentian PSBB Surabaya Raya di Media Online kompas.com dan suarasurabaya.net - Ruri Handariastuti; Zainal Abidin Achmad; Airlangga Bramayudha (Program Studi Ilmu Komunikasi Fakultas Dakwah dan Komunikasi, UIN Sunan Ampel Surabaya, 2020)
This research discusses the Analysis of the News Framing of PSBB Surabaya Raya Termination in Online Media Kompas.com and Suarasurabaya.net Edition 8-9 June 2020. This research uses constructive paradigm using Framing Pan and Kosicki analysis method with the assumption that each news article has a frame which functions as a center of the organizational idea. Kompas.com dan suarasurabaya.net have their own views to frame their news. Kompas.com is a national online media, while for suarasurabaya.net is a local online media that much people interest in Surabaya, especially for radio media. The result shows news article has used some of them have a lack point and suarasurabaya.net more construct East Java Governor figure.